PENYUSUNAN BAHAN AJAR TERINTEGRASI NILAI RELIGI PADA SISTEM PENCERNAAN MANUSIA SEBAGAI UPAYA MENINGKATKAN SIKAP DAN PENGUASAAN KONSEP SISWA SMA - Enuy Nurjanah, - (2018)
This study aims to compile teaching materials integrated religious values in the human digestive system as an effort to improve the attitude and mastery of the concept of high school students. Research design used Research & development which includes the process of defines, design, develop and disseminate. The process of define (preliminary) through preliminary studies, analyzing core competence (KI), basic competence (KD) and literature study. Design chooses and determines teaching materials, creates microstructures, macro structures of teaching materials and compiles religious values. The development stage includes the preparation of teaching materials and validation of teaching materials. Validation aims to assess the quality of teaching materials conducted by biologists, religious scholars, lay outers and textbook editors, biology teachers and students. Validation of feasibility of teaching materials by material experts, lay outers / editors and biology teachers using closed questionnaires and validation of religious experts using open fields. Readability analysis using the cloze test. Student attitudes are measured using Likert's attitude scale, and mastery of concepts is measured using an instrument of conceptual mastery. The results of the assessment of material experts are in the category of very strong feasibility, the results of expert judgments of teaching materials worthy to be tested with revised terms related to citation of the wrong verse. The results of expert assessment lay outers / editors are in the category of strong feasibility and test readings results have a high level of readability. The results of the teaching materials implementation showed that the teaching materials can improve the mastery of the concept of the attitude category to be very good, and can improve the students' concept of comprehension significantly. Students' responses to learning materials and integrated learning of religious values on the human digestive system are very strong categories.---- Penelitian ini bertujuan untuk menyusun bahan ajar sistem pencernaan manusia terintegrasi nilai religi sebagai upaya untuk meningkatkan sikap siswa dalam menghadapi masalah terkait konsep sistem pencernaan dan penguasaan konsep siswa SMA. Desain penelitian yang digunakan Research& development yang meliputi proses define, design, develop dan disseminate. Proses define (pendahuluan) melalui studi awal, menganalisis KI dan KD dan studi literatur. Design (perancangan) memilih dan menentukan bahan ajar, membuat struktur mikro, strukturmakro bahan ajar dan mengkompilasi nilai religi. Tahap develop (Pengembangan) meliputi penyusunan bahan ajar dan validasi terhadap bahan ajar.Validasi bertujuan untuk menilai kualitas bahan ajar dilakukan oleh ahli materi biologi, ahli agama, ahli layouter dan editor buku pelajaran, guru Biologi dan siswa. Validasi kelayakan bahan ajar menggunakan angket tertutup dan isian terbuka. Analisis keterbacaan menggunakan uji Rumpang (Cloze test). Sikap siswa diukur menggunakan skala Likert, dan penguasaan konsep diukur menggunakan instrumen soal penguasaan konsep. Hasil penilaian ahli materi berada pada kategori kelayakan sangat kuat, hasil penilaian ahli agama bahan ajar layak diujicobakan dengan syarat direvisi terkait pengutipan ayat yang kurang tepat. Hasil penilaian ahli layouter/editor berada pada kategori kelayakan kuat dan hasil tes uji ketebacaan bahan ajar memiliki tingkat keterbacaan yang tingi. Hasil implementasi bahan ajar menunjukkan bahan ajar dapat meningkatkan penguasaan konsep dari kategori sikap cukup menjadi sangat baik, dan dapat meningkatkan penguasaan konsep siswa secara signifikan. Tanggapan siswa terhadap bahan ajar dan pembelajaran terintegrasi nilai religi pada sistem pencernaan manusia berkategori sangat kuat.